Determinants of knowledge and technology transfer activities between firms and science institutions in Switzerland: An analysis based on firm data - Spyros Arvanitis; Ursina Kubli; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2005)
This study explores the factors determining the propensity of Swiss firms to interact with public science institutions in Switzerland (universities and other research institution), i.e. to get involved in knowledge and technology transfer (KTT) activities in order to gain new tacit and/or codified scientific knowledge in research fields which are relevant for their own innovation activities. We are especially interested in the different forms of this interaction, not only through joint research projects but also through training, recruitment of qualified R&D personnel, jointly supervised master theses and PhDs, consulting and so on. The data used in this study were collected in the course of a survey among Swiss enterprises. The new elements that this paper adds to empirical literature are, first, the analysis of a wide spectrum of KTT activities covering not only research co-operation agreements between firms and science institutions but also general informational and educational activities (transfer of tacit knowledge), joint use of technical infrastructure and consulting. Although such additional activities seem to be an important part of KTT activities, they have been neglected in most studies. Second, a further important element is the explicit consideration of a series of relevant motives and obstacles as determinants of KTT which contribute significantly to the econometric explanation of firms' propensity to overall KTT activities as well as to several forms of KTT activities. Third, some insights are gained with respect to the differences between manufacturing and service firms in transacting with science institutions. This is the first Swiss firm-level study on this matter.
Keywords: O30; 330; knowledge and technology transfer; innovation activities; R&D activities; Forschungskooperation; Wissenstransfer; Schweiz